Tumor Necrosis Factor -α, Interleukin-10, Intercellular and Vascular Adhesion Molecules Are Possible Biomarkers of Disease Severity in Complicated Plasmodium vivax Isolates from Pakistan - Raza, Afsheen (Public Library of Science, 2013)
BACKGROUND: Cytokine-mediated endothelial activation pathway is a known mechanism of pathogenesis employed by Plasmodium falciparum to induce severe disease symptoms in human host. Though considered benign, complicated cases of Plasmodium vivax are being reported worldwide and from Pakistan. It has been hypothesized that P.vivax utilizes similar mechanism of pathogenesis, as that of P.falciparum for manifestations of severe malaria. Therefore, the main objective of this study was to characterize the role of cytokines and endothelial activation markers in complicated Plasmodium vivax isolates from Pakistan. METHODS AND PRINCIPLE FINDINGS: A case control study using plasma samples from well-characterized groups suffering from P.vivax infection including uncomplicated cases (n=100), complicated cases (n=82) and healthy controls (n=100) were investigated. Base line levels of Tumor necrosis factor-α (TNF-α), Interleukin-6 (IL-6), Interleukin-10 (IL-10), Intercellular adhesion molecule-1 (ICAM-1), Vascular adhesion molecule-1(VCAM-1) and E-selectin were measured by ELISA. Correlation of cytokines and endothelial activation markers was done using Spearman’s correlation analysis. Furthermore, significance of these biomarkers as indicators of disease severity was also analyzed. The results showed that TNF-α, IL-10, ICAM-1and VCAM-1 were 3-fold, 3.7 fold and 2 fold increased between uncomplicated and complicated cases. Comparison of healthy controls with uncomplicated cases showed no significant difference in TNF-α concentrations while IL-6, IL-10, ICAM-1, VCAM-1 and E-selectin were found to be elevated respectively. In addition, significant positive correlation was observed between TNF-α and IL-10/ ICAM-1, IL-6 and IL-10, ICAM-1 and VCAM-1.A Receiver operating curve (ROC) was generated which showed that TNF-α, IL-10, ICAM-1 and VCAM-1 were the best individual predictors of complicated P.vivax malaria. CONCLUSION: The results suggest that though endothelial adhesion molecules are inducible by pro-inflammatory cytokine TNF-α, however, cytokine-mediated endothelial activation pathway is not clearly demonstrated as a mechanism of pathogenesis in complicated P.vivax malaria cases from Pakistan.